Modification of Asparagine-Linked Glycan Density for the Design of Hepatitis B Virus Virus-Like Particles with Enhanced Immunogenicity - Hyakumura, Michiko (J Virol, 2015)
The small envelope proteins (HBsAgS) derived from hepatitis B virus (HBV) represent the antigenic components of the HBV vaccine and are platforms for the delivery of foreign antigenic sequences. To investigate structure-immunogenicity relationships for the design of improved immunization vectors, we have generated biochemically modified virus-like particles (VLPs) exhibiting glycoengineered HBsAgS. For the generation of hypoglycosylated VLPs, the wild-type (WT) HBsAgS N146 glycosylation site was converted to N146Q; for constructing hyperglycosylated VLPs, potential glycosylation sites were introduced in the HBsAgS external loop region at positions T116 and G130 in addition to the WT site. The introduced T116N and G130N sites were utilized as glycosylation anchors resulting in the formation of hyperglycosylated VLPs. Mass spectroscopic analyses showed that the hyperglycosylated VLPs carry the same types of glycans as WT VLPs, with minor variations regarding the degree of fucosylation, bisecting N-acetylglucosamines, and sialylation. Antigenic fingerprints for the WT and hypo- and hyperglycosylated VLPs using a panel of 19 anti-HBsAgS monoclonal antibodies revealed that 15 antibodies retained their ability to bind to the different VLP glyco-analogues, suggesting that the additional N-glycans did not shield extensively for the HBsAgS-specific antigenicity. Immunization studies with the different VLPs showed a strong correlation between N-glycan abundance and antibody titers. The T116N VLPs induced earlier and longer-lasting antibody responses than did the hypoglycosylated and WT VLPs. The ability of nonnative VLPs to promote immune responses possibly due to differences in their glycosylation-related interaction with cells of the innate immune system illustrates pathways for the design of immunogens for superior preventive applications. IMPORTANCE The use of biochemically modified, nonnative immunogens represents an attractive strategy for the generation of modulated or enhanced immune responses possibly due to differences in their interaction with immune cells. We have generated virus-like particles (VLPs) composed of hepatitis B virus envelope proteins (HBsAgS) with additional N-glycosylation sites. Hyperglycosylated VLPs were synthesized and characterized, and the results demonstrated that they carry the same types of glycans as wild-type VLPs. Comparative immunization studies demonstrated that the VLPs with the highest N-glycan density induce earlier and longer-lasting antibody immune responses than do wild-type or hypoglycosylated VLPs, possibly allowing reduced numbers of vaccine injections. The ability to modulate the immunogenicity of an immunogen will provide opportunities to develop optimized vaccines and VLP delivery platforms for foreign antigenic sequences, possibly in synergy with the use of suitable adjuvanting compounds.